Strategi Ketahanan Pangan Berkelanjutan di Jawa Tengah: Menangani Inflasi, Kemiskinan dan Kekurangan Gizi - Pujiyanto, Muhammad Aris; Setyorini, Fitri Adi; Azizi, Ernes Septina; Cahyaningsih, Anggi Fitria; Solekan, Muhamad (LPPM Universitas Malikussaleh - Indonesia, 2025)
This study examines sustainable food security strategies in Central Java, focusing on addressing the interrelated issues of inflation, poverty, and undernourishment. Through a systematic literature review, the research identifies effective approaches such as conditional cash transfers, public distribution systems, agricultural extension services, and community-based nutrition programs, which have been successfully implemented in other regions. The findings suggest that these strategies can be adapted to the local context in Central Java, with specific emphasis on enhancing food accessibility, improving nutritional outcomes, and promoting agricultural productivity. The proposed policies align with the strategic objectives outlined in the RENSTRA Dinas Ketahanan Pangan Provinsi Jawa Tengah 2024-2026, including the development of rural infrastructure, strengthening food distribution systems, and integrating nutrition interventions into existing healthcare services. The study highlights the importance of a coordinated, multi-sectoral approach to effectively tackle food security challenges in Central Java, ensuring that interventions are sustainable and impactful in reducing poverty and improving public health outcomes. This research provides a framework for policymakers in Central Java to design and implement comprehensive food security strategies that are both practical and aligned with regional development goals.